2012
DOI: 10.5539/ass.v9n1p271
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Experiential Reflections on Iranian and Malaysian Students’ Collaborative Orientations

Abstract: This paper is part of a larger study which was concerned with the comparison and description of Iranian and Malaysian students' classroom behaviors in general and their collaborative tendencies in particular. In this paper the core findings of interviews with five teachers who had the experience of teaching both in the contexts of Iran and Malaysia are reported. They all shared the view that the collectivist orientation is tangibly stronger among Malaysian participants than among their Iranian counterparts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Among others, Hofstede (1991) identified that Malaysians and Iranians differ along the dimension of individualism/collectivism. Indeed, Amirkhiz et al (2013) found that Malaysians are more collectivist than Iranians, although they are grouped as collectivist.The higher purchase intentions among Malaysian participants could possibly be explained by the nature of a collectivist culture (e.g. De Run et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among others, Hofstede (1991) identified that Malaysians and Iranians differ along the dimension of individualism/collectivism. Indeed, Amirkhiz et al (2013) found that Malaysians are more collectivist than Iranians, although they are grouped as collectivist.The higher purchase intentions among Malaysian participants could possibly be explained by the nature of a collectivist culture (e.g. De Run et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there have always been concerns if collaborative activities are necessarily compatible with ELT practice in all contexts and for different cultures. Knowing that many of Iranian EFL learners, based on their cultural beliefs and upbringings, are not really interested in collaborative activities (Amirkhiz, Bakar, Mahmoudi, 2013), it can be legitimate to state that the significance of MS over CSR, as reported in this study, might have been contributed to, at least to some extent, by participants' cultural beliefs and the peculiarities of the context.…”
Section: Discussionmentioning
confidence: 73%
“…A model of dyadic interaction (Storch, 2002, p. 128) collaborative orientations they produced more LREs and achieved higher posttest scores. Kim and McDonough's (2008) Additional factors, such as the primary pedagogical focus of learners' language program (Loewen, 2004), previous L2 instruction experiences (Amirkhiz et al, 2013) and…”
Section: Factors Influencing the Production Of Collaborative Dialoguementioning
confidence: 99%